"How to say no without saying no" - Farawila, Sherif Ezzat (AUC Knowledge Fountain, 2019)

(untitled)
This study investigates the realization and perception of the speech act of refusal among German Learners of Arabic as a Foreign Language and native Egyptian speakers cross-culturally. Besides, it examines the extent of pragmatic transfer from L1 and its nature of being negative or positive one. Three groups participated in the study: eight native speakers of Egyptian Arabic, eight AFL German learners, and three native speakers of German. The data were collected using enhanced open-ended role plays. Furthermore, to increase the creditability of the interaction data, the study triangulated the data by utilizing retrospective verbal reports. Both quantitative and qualitative methods were employed for analyzing the interactions. Results show essential differences between Egyptians and German AFL learners concerning the frequency of direct and indirect strategies and the utilization of individual strategies. For example, German AFL learners employed a higher percentage of indirect strategies and a lower percentage of direct strategies than the native speakers of Egyptian Arabic, especially in higher status situations. Moreover, German AFL learners used a higher percentage of the Statement of Regret and Request for Information/Clarification strategies than the native Egyptians. However, the native Egyptians have utilized a higher percentage of indirect strategies than the AFL group within the deference relations. Comparing the pattern of refusal strategy of the three groups reveals evidence of positive and negative pragmatic transfer in the AFL group. Social factors differences, during the interactions, were found to play a significant role in how refusals were realized in both cultures. From a pedagogical point of view, the results imply that refusals are worth incorporating and be integrated into the language curriculum. That is, AFL learners not only need to recognize the linguistic forms necessary to produce the speech act, but they must be aware of sociocultural values that characterize the target speech community of the target Language. Therefore, the study suggests that AFL teachers should be aware of the significant role of pragmatic variation when teaching pragmatics inside the classroom. This awareness could be reflected by focusing on awareness-raising activities at the cognitive level, production activities for the speech act of refusals, and teaching grammar as a communicative resource to encourage AFL to produce refusals according to the different sociocultural values of the target Language.